Redefining avoidable and inappropriate admissions. (January 2022) - Clubbs Coldron, B.; MacRury, S.; Coates, V.; Khamis, A.
Abstract: Objectives: Focusing on policy discourse in the United Kingdom, we examine the chain of causation that is characteristic of the ways in which the concepts of avoidability and inappropriateness are defined and used in these contexts. With a particular focus on diabetes complications, we aim to elucidate the way in which avoidable admission to hospital is conceptualised, measured, and applied to policy development and implementation and build a more inclusive model of identification as a basis for further research in this area. Study design: Discourse analysis was used in combination with a scoping review. Methods: We searched the online databases of the UK Houses of Parliament Hansard, Official reports of the Northern Ireland Assembly and transcripts of the Scottish Parliament in October 2021. We also conducted an electronic search in October 2021 on MEDLINE, PubMed, Google Scholar, EMBASE, CINAHL and The Cochrane Library to review the available literature. In addition, an analysis of policies in place in Scotland, England and Northern Ireland relating to urgent diabetes care was conducted. Results: 'Avoidable' and 'inappropriate' hospital admissions are categories used in health policy and practice internationally as ways of identifying targets for interventions intending to reduce the burden of care. Diabetes mellitus is a chronic condition that is often seen as a costly and avoidable use of health care services and so is a frequent target of such policies. Avoidable admission is interpreted as having a very long chain of causation. The assumption is that people requiring unscheduled hospital admission could have taken steps to prevent the onset of diabetes, or associated complications, arising in the first place. Definitions focus on primary and secondary prevention and largely place responsibility on the individual and their behaviour rather than on structural or social factors. Inadequate or inappropriate care prehospital or in the emergency department is seldom considered as a potential cause of avoidable admissions. Procedural definitions of avoidable admission are proposed whereby health care professionals and people living with diabetes collaborate to identify avoidable admissions in clinical audit rather than using statistical rates of avoidable admission within isolation in policy development and implementation. Conclusions: Avoidability and inappropriateness are characteristics of cases in which conduct of the individual or attendant health care professionals was a proximate cause of hospital admission, and but for such conduct, admission could have been avoided. This process of definition seeks to provide a basis for contextualised and considered evaluation of where there are problems in care and where there are reasonable opportunities for prevention.